2006
DOI: 10.1182/blood-2005-06-2452
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between NF-κB family members p50 and p52 is essential for mediating LTβR signals in the development and organization of secondary lymphoid tissues

Abstract: Recent studies revealed that the lymphotoxin/lymphotoxin beta receptor (LT)/ LT␤R system activates the noncanonical nuclear factor-B (NF-B) signaling pathway involving I kappa B kinase 1/I kappa B kinase ␣ (IKK1/IKK␣) and NF-B-inducing kinase (NIK) to direct processing of the nfb2 protein p100 to yield RelB:p52 complexes. Despite the biochemical evidence, LT-, RelB-, p52-deficient mice show discrepant phenotypes. We now demonstrate that p105/p50 also constitutes an important pathway for LT␤R signaling. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 40 publications
(71 reference statements)
11
91
0
Order By: Relevance
“…Lymph nodes are located throughout the body to monitor the draining fluids and migrating lymphocytes for pathological changes (Lo et al, 2006;Mebius, 2003). The ltbr -/-mice demonstrated that lymphotoxin-β receptor (LTβR) signaling critically regulates lymph node formation (Futterer et al, 1998;Rennert et al, 1998).…”
Section: Secondary Lymphoid Organ Development Via the Ltβrmentioning
confidence: 99%
See 4 more Smart Citations
“…Lymph nodes are located throughout the body to monitor the draining fluids and migrating lymphocytes for pathological changes (Lo et al, 2006;Mebius, 2003). The ltbr -/-mice demonstrated that lymphotoxin-β receptor (LTβR) signaling critically regulates lymph node formation (Futterer et al, 1998;Rennert et al, 1998).…”
Section: Secondary Lymphoid Organ Development Via the Ltβrmentioning
confidence: 99%
“…Analysis with radiation chimeras suggested a requirement for RelA within the nonhematopoietic stromal cells for the development of secondary lymphoid organs (Alcamo et al, 2002). Similarly, p50-deficient mice exhibited defects in lymphoid tissues with a loss of inguinal lymph nodes (Lo et al, 2006). A requirement of the RelA:p50 dimer in stromal cells for activating VCAM-1 or ICAM-1 gene expression during LTβR signaling (Dejardin et al, 2002;Lo et al, 2006) was proposed to be responsible for these lymph node phenotypes.…”
Section: Requirement Of Rela and P50 In The Lymph Node Developmentmentioning
confidence: 99%
See 3 more Smart Citations